APPLICATION OF THE NEW TOTW LEARNING MODEL TO IMPROVE THE CREATIVE THINKING ABILITY OF HIGH SCHOOL STUDENTS ON BUFFER SOLUTION MATERIALS - Haryanto, Haryanto; Ernawati, M. Dwi Wiwik; Intan, Intan; Widowati, Atri; Kurniawan, Imam (LPPM Universitas Jambi, 2025)
This study aims to analyze the effect of the implementation of the Think, Observe, Talk, and Write (TOTW) learning model on students' creative thinking skills on buffer solution material. The method used is a quasi-experiment with a Non-Equivalent Control Group Design, involving two sample classes, namely the experimental class and the control class at Senior High School Islam Al-Falah, Jambi. The research instruments include essay tests and observation sheets covering aspects of sensitivity, fluency, flexibility, originality, and elaboration. Data were analyzed using statistical tests to test the hypothesis. The results showed that the implementation of the TOTW model significantly improved students' creative thinking skills, with the average posttest of the experimental class being higher than the control class. In addition, the observation results indicated an increase in creative thinking skills in the experimental class in all aspects assessed. Statistical tests showed a significant effect of the implementation of the TOTW model on students' creative thinking skills. This study concludes that the TOTW model is effective in improving students' creative thinking skills, especially on materials that require conceptual understanding such as buffer solutions. The implications of this study include recommendations for the implementation of innovative learning models in various learning contexts to support the development of students' high-level thinking skills.